Fragmented water management threatens Cambodia's Mekong delta food security: AMD Initiative pushes integrated approach - Sok, Sao; Bernardo, Eisen; Sithirith, Mak (CGIAR, 2024)
Cambodia’s Mekong Delta faces a food security crisis driven by climate change, population growth, and fragmented water and land management, affecting irrigation, fisheries, eco-tourism, and agriculture cooperatives. The CGIAR Initiative on Asian Mega-Deltas (AMD) promotes integrated governance to enhance food systems through decentralized planning across sectors and hydrological units. AMD collaborates with ministries and local authorities, piloting integrated district-level food governance to ensure sustainable agriculture, fisheries, and resource management. A policy brief recommends diversifying diets, unifying water-land strategies, and fostering community inclusion. Recent ministerial collaboration aims to align sectoral efforts, strengthen food system governance, and enhance climate resilience.